2001
DOI: 10.5326/15473317-37-6-553
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial metastases from an ovarian dysgerminoma in a 2-year-old dog

Abstract: A 2-year-old, intact female rottweiler was presented for signs of lethargy. A mass was ultrasonographically observed, cranial and lateral to the left kidney. Exploratory laparotomy revealed a mass in the left ovary that was diagnosed histopathologically as an ovarian dysgerminoma. Two weeks after surgery, the dog was readmitted with signs of peripheral vestibular disease that progressed to central vestibular disease. Magnetic resonance imaging of the brain revealed the presence of a mass in the caudal fossa. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…In 1 retrospective study, the authors found that dysgerminomas develop in dogs ≥10 years old, whereas teratomas develop in dogs ≤9 years old 17. Metastasis is reported to develop in 10–20% of cases,1 with regional lymph nodes, liver, brain,19 and kidney as the primary sites of metastasis. Abdominal effusion may develop in association with this neoplasm 8…”
Section: Discussionmentioning
confidence: 99%
“…In 1 retrospective study, the authors found that dysgerminomas develop in dogs ≥10 years old, whereas teratomas develop in dogs ≤9 years old 17. Metastasis is reported to develop in 10–20% of cases,1 with regional lymph nodes, liver, brain,19 and kidney as the primary sites of metastasis. Abdominal effusion may develop in association with this neoplasm 8…”
Section: Discussionmentioning
confidence: 99%
“…Dysgerminoma is an uncommon ovarian tumour in domestic animals, but it has been reported in most species and most frequently in dogs (MacLachlan 1987). Dysgerminoma has its origin in primordial germ cells of the embryonic gonad and it resembles testicular seminoma in males (Fernández et al. 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of secondary brain tumors may be increasing because animals with systemic malignancies are now being treated more aggressively with chemotherapeutic agents that prolong lifespan, allowing more time for intracranial metastasis to occur 1 . Alternatively, the incidence of secondary tumors of the brain may have been underrepresented previously because the cranial vault was not routinely examined as a metastatic site 3,4 . In dogs, carcinomas account for the majority of reported brain metastases, followed by sarcomas 1,5…”
mentioning
confidence: 99%
“…1 Alternatively, the incidence of secondary tumors of the brain may have been underrepresented previously because the cranial vault was not routinely examined as a metastatic site. 3,4 In dogs, carcinomas account for the majority of reported brain metastases, followed by sarcomas. 1,5 Although intracranial neoplasia is well described in the dog, few reports in this species have focused on secondary tumors of the brain.…”
mentioning
confidence: 99%